Safety and efficacy of an equimolar mixture of oxygen and nitrous oxide: a randomized controlled trial in patients with peripheral neuropathic pain. Issue 4 (April 2021) - Bouhassira, Didier; Perrot, Serge; Riant, Thibault; Martiné-Fabre, Gaelle; Pickering, Gisèle; Maindet, Caroline; Attal, Nadine; Ranque Garnier, Stéphanie; Nguyen, Jean-Paul; Kuhn, Emmanuelle; Viel, Eric; Kieffert, Patrick; et al.
Abstract : Abstract: Nitrous oxide (N2 O) is an odorless and colorless gas routinely used as an adjuvant of anesthesia and for short-duration analgesia in various clinical settings mostly in the form of an N2 O/O2 50%-50% equimolar mixture (EMONO). Experimental studies have suggested that EMONO could also induce long-lasting analgesic effects related to the blockade of N-methyl-D-aspartate receptors. We designed the first international multicenter proof of concept randomized, placebo-controlled study to assess the efficacy and safety of a 1-hour administration of EMONO or placebo (medical air) on 3 consecutive days up to 1 month after the last administration in patients with chronic peripheral neuropathic pain. A total of 240 patients were recruited in 22 centers in France and Germany and randomly assigned to 1 study group (120 per group). Average pain intensity (primary outcome), neuropathic pain characteristics (Neuropathic Pain Symptom Inventory), Patient Global Impression of Change, anxiety, depression, and quality of life were systematically assessed before and after treatment. The changes in average pain intensity between baseline and 7 days after the last administration were not significantly different between the 2 groups. However, evoked pain intensity (predefined secondary endpoint) and Patient Global Impression of Change (exploratory endpoint) were significantly improved in the EMONO group, and these effects were maintained up to 4 weeks after the last treatment administration. Mostly transient side effects were reported during the treatment administration. These encouraging results provide a basis for further investigation of the long-term analgesic effects of EMONO in patients with neuropathic pain. Abstract : Nitrous oxide–oxygen mixture inhalations had no significant effects on average pain intensity, but seemed to reduce evoked pain intensity in patients with peripheral neuropathic pain.